Elements of the Lattice Boltzmann Method II: Kinetics and Hydrodynamics in One Dimension (Communications in Computational Physics, 2018)
Concepts of the lattice Boltzmann method are discussed in detail for the one-dimensional kinetic model. Various techniques of constructing lattice Boltzmann models are discussed, and novel collision integrals are derived. Geometry of the kinetic space and the role of the thermodynamic projector is elucidated.